Analisis Angkutan Sedimen Sungai Batang Kuranji Di Kota Padang Menggunakan HEC-RAS 6.1 - Sujatmoko, Bambang; Mintio, Reygi Raica; Fauzi, Manyuk (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2024)
Sedimentation is one of the problems that often occurs in rivers. Sedimentation that occurs continuously will cause siltation of the riverbed so that it can cause flooding due to reduced cross-sectional capacity of the river. Understanding these conditions, this study was conducted to examine the distribution of sediment transport that occurs in rivers. The river that is the location of the study is Batang Kuranji River which is located in the city of Padang, West Sumatra. HEC-RAS version 6.1 was used to model and simulate the sediment transport process. Simulations were carried out with a duration of 100 days and three flow conditions, flood discharge at return times of 2, 5 and 10 years. The sediment transport function used is the Meyer Peter-Muller equation. The results indicate the occurrence of sedimentary material deposits scattered throughout the study location. The total volume of sediment deposit in flood discharge conditions for 2, 5 and 10 years, respectively, is 6,978 m3; 2,989 m3 and 132 m3. The highest sediment deposit occurred in the simulation with a 10-year return period discharge at RS 14 (STA 1+350) which was 5,141,533 m3. After analysis, the high sediment deposition in the Batang Kuranji river section is caused by a decrease in flow velocity due to the influence of tides at the river estuary.